Performance Assessment Development of Ternate Tidore Protected Forest Management Unit, of North Moluccas Province - Mansyur, Fitri; Salim , Tamrin; Julham , Muhammad (Agrikan Jurnal Agribisnis Perikanan, 2025)
Forest Management Unit (KPH) is a forest management area according to its main function and designation that can be managed efficiently and sustainably. KPH was formed to present an effective and efficient forest management unit at the site level. This research was conducted from April to July 2024, the data in this study includes Primary Data and Secondary Data, Data collection was carried out by Field Observation, Interviews, and documentation from several related literatures. The informants in this study were determined by Purposive sampling, The research informant was the Head of KPH Ternate-Tidore, Data analysis in this study used Descriptive methods (qualitative and quantitative). The results of this study indicate that the performance assessment that has been carried out, the average index value of the 8 criteria is 2.59, the index value is in the high category which means that KPH Ternate - Tidore in its implementation has realized its function as a forest management unit at the site level. However, several criteria need to be improved so that in the future, KPH Ternate Tidore can be more optimal in realizing its function in managing forests at the site level.